"Flesh and Blood Archives": Embodying the Oral History Transcript. (1st April 2018) - Cheng, Nien Yuan
Abstract: There is a burgeoning discussion in oral history about the nature of embodiment in the oral history interview and how we might include considerations of this embodiment in the process and products of oral history. This article suggests ways in which interviewers can "embody" the interview transcript with evocative written description; it uses transcribed excerpts and audio clips of an interview conducted by the author to illustrate both what to include in an embodied transcript, and what to keep in mind when undertaking the tricky business of translating the multidimensional interview encounter to the two-dimensional page. Note on Multimedia Content : The online version of this article, doi:10.1093/ohr/ohx071, includes audio and video clips that allow readers to see or listen to excerpts of recorded interviews. In the HTML version, readers may simply click and play; in the PDF version, it is necessary first to download the PDF.